ANALISIS BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Estiana, Ria; Pramulanto, Himawan (JAB (Jurnal Akuntansi & Bisnis), 2020)
ABSTRACTÂ This study aims to determine the effect of organizational culture on the performance of PT.Mitrametal Perkasa employees, Karawang. Organizational culture can be seen in part from an organizational environment that affects the behavior and appearance (performance) of employees in the organization.This research is a quantitative study using a survey method with data collection techniques using a questionnaire. The population in this study were all employees of PT.Mitrametal Perkasa, Karawang, sampling using a saturated sampling technique that is all employees totaling 1076 people. The data analysis technique uses correlation test. The results of this study indicate that organizational culture affects employee performance at 62.9%.Â Keywords: organizational culture, employee performance